Community-Based Social Education for Sustainable Development – An Indonesian Perspective on Collaborative Learning Models - Vann, Rithy; Rith, Vicheka; Suyitno, Suyitno (Journal Neosantara Hybrid Learning, 2025)
Community-based social education plays a crucial role in fostering sustainable development, especially in countries with diverse social structures such as Indonesia. However, the implementation of collaborative learning models within this framework remains underexplored. This study aims to investigate the effectiveness of community-based social education in supporting sustainable development through the application of collaborative learning models from an Indonesian perspective. Employing a qualitative research method with a case study approach, data were collected through interviews, focus group discussions, and observations involving educators, community leaders, and learners in selected rural and urban communities. The findings reveal that collaborative learning models significantly enhance community engagement, improve critical thinking skills, and promote shared responsibility among participants. Furthermore, the integration of local wisdom and cultural values into learning processes strengthens the relevance and sustainability of educational programs. The study concludes that community-based social education, when supported by well-structured collaborative learning models, can serve as an effective strategy for achieving sustainable development goals. It emphasizes the need for policy support, capacity building, and continuous evaluation to ensure the scalability and impact of such educational initiatives.